Bridging the atomic divide : debating Japan-US attitudes on Hiroshima and Nagasaki - Wray, Harry, 1931- (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2019)
"In this study, two scholars examine historical perceptions of the atomic bombings of Hiroshima and Nagasaki. Structured as a balanced dialogue, the authors analyze how the attacks are remembered by Japanese and others as well as the various debates surrounding the bombings."--Provided by publisher.